Participation in life situations of 8-12 year old children with cerebral palsy: cross sectional European study. (24th April 2009) - Fauconnier, Jérôme; Dickinson, Heather O; Beckung, Eva; Marcelli, Marco; McManus, Vicki; Michelsen, Susan I; Parkes, Jackie; Parkinson, Kathryn N; Thyen, Ute; Arnaud, Catherine; Colver, Allan
Abstract : Objectives To evaluate how involvement in life situations (participation) in children with cerebral palsy varies with type and severity of impairment and to investigate geographical variation in participation. Design Cross sectional study. Trained interviewers visited parents of children with cerebral palsy; multilevel multivariable regression related participation to impairments, pain, and sociodemographic characteristics. Setting Eight European regions with population registers of children with cerebral palsy; one further region recruited children from multiple sources. Participants 1174 children aged 8-12 with cerebral palsy randomly selected from the population registers, 743 (63%) joined in the study; the further region recruited 75 children. Main outcome measure Children's participation assessed by the Life-H questionnaire covering 10 main areas of daily life. Scoring ignored adaptations or assistance required for participation. Results Children with pain and those with more severely impaired walking, fine motor skills, communication, and intellectual abilities had lower participation across most domains. Type of cerebral palsy and problems with feeding and vision were associated with lower participation for specific domains, but the sociodemographic factors examined were not. Impairment and pain accounted for up to a sixth of the variation in participation. Participation on all domains varied substantially between regions: children in east Denmark had consistently higher participation than children in other regions. For most participation domains, about a third of the unexplained variation could be ascribed to variation between regions and about two thirds to variation between individuals. Conclusions Participation in children with cerebral palsy should be assessed in clinical practice to guide intervention and assess its effect. Pain should be carefully assessed. Some European countries facilitate participation better than others, implying some countries could make better provision. Legislation and regulation should be directed to ensuring this happens.